The early bird in renal rescue: timing matters in acute kidney injury management—insights from target trial emulation - She, Miaowen; Zhuang, Jinhu; Chen, Xi; Hu, Lili; Thach, Thuan-Quoc; Cheung, Kin; Yu, Xiaxia; Wang, Mengyi; Zheng, Xiang; Liu, Yong (Frontiers in Medicine, 2025)
BackgroundAcute kidney injury (AKI) is prevalent in critically ill patients. The optimal timing for initiating renal replacement therapy (RRT) remains unsettled. Clinical intuition suggests early initiation could be beneficial, but evidence from studies is inconsistent.MethodsA target trial emulation was conducted using the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. Two cohorts were analyzed: broader cohort (stage ≥1, N = 7,607) and severe cohort (stage 3, N = 943). Cox proportional hazards models with inverse probability weighting (IPW) were used to estimate the causal effect on 90-day and 30-day mortality, with sensitivity analyses using accelerated failure time models and augmented inverse probability weighting.ResultsIn the broader cohort, early initiation was associated with lower 90-day (hazard ratio (HR): 0.653, 95% confidence interval (CI): 0.512–0.834) and 30-day mortality (HR 0.649, 95% CI 0.504–0.835). However, accelerated failure time models indicated no survival benefit and potentially worse outcomes, with a 14.8% reduction in 90-day survival and a 14.1% reduction in 30-day survival. Augmented inverse probability weighting (AIPW) analysis further confirmed these findings, showing a risk difference of 2.6 percentage points between early and late initiation of RRT. In the severe cohort, early initiation was associated with lower 90-day mortality (HR: 0.561, 95% CI: 0.341–0.921) and 30-day mortality (HR: 0.604, 95% CI: 0.357–1.022), with accelerated failure time models confirming longer survival. Augmented inverse probability weighting analysis in this group showed a risk difference of 1.7 percentage points.ConclusionEarly initiation appears beneficial in the severe cohort (stage 3), but not in the broader cohort (stage ≥1), where it could even be harmful. This highlights the need for personalized treatment based on the severity of acute kidney injury and further research to optimize the timing of renal replacement therapy.